Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Ventilation strategies for mold control during egg storage and transportation: A comprehensive evaluation integrating ITS sequencing and antibacterial efficacy - Wenbin Zhou; Yuanhang Shi; Yu Liu; Lin Xuan; Xuefeng Shi; Runzhe Wang; Jiajie Yang; Zhanpeng Wang; Junying Li; Guiyun Xu; Jiangxia Zheng (Food Control, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Postharvest properties and metabolomic profiling of cucumbers treated with hydrogen sulfide under low-temperature storage - Wei Han Foo; Mingmin Chen; Xue Zhao; Yu Xuan Lim; Lin Chen (Food Chemistry, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Machine-learning-guided extraction optimization and physicochemical characteristic of GRAS microalgae proteins for sustainable food applications - Wei Han Foo; Mingmin Chen; Yu Xuan Lim; Lin Chen (Food Hydrocolloids, 2026)

Decoupling Risks in the Fringe: An Integrated SOM-PMF Framework for Spatially-Explicit PFAS Source Apportionment Across Surface–Groundwater Interfaces - Xuan Lin; Shengpin Yu; Dandan Huang; Yiwen Pan; Zehui Zhang; Li Zhang; Chunyu Yan; Xiaolu Liu; Bai Gao; Yuanyuan Liu; Wenjie Ma (Water, Air, & Soil Pollution, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Improved method for adjusting natural frequency of structures via stacked piezoelectric ceramic actuators - Wei Lin; Chaodong Xue; Yingjie Ren; Xuan Yao; Yu Zhang; Xiongliang Yao (Ocean Engineering, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Enhanced fluoxetine removal from water via Fe/Cu-doped biochar-activated percarbonate under sunlight and aeration - Yang Wu; Zhi-hao Li; Xi-xi Lu; Zi-xuan Lin; Chang-ping Yu (Journal of Environmental Chemical Engineering, 2026)

A bezafibrate bearing Pt(IV) prodrug triggers ferroptosis via modulating lipid metabolism in lung cancer cells - Neng Wan; Xuan-Lin Ren; Xiang-Yu Ma; Tao Zhu; Cheng-Zhi Xie; Jing-Yuan Xu; Xin Qiao (JBIC Journal of Biological Inorganic Chemistry, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

Advances in thermoelectric coupling catalysis for CO2 reduction: Synergistic mechanisms, catalyst development, and application perspectives - Mengke Niu; Lei Wang; Linjie Cai; Jia Liu; Xuan Lin; Jun Yu; Sam Toan; Zhaoteng Xue; Dongsen Mao (Journal of Environmental Chemical Engineering, 2025)

Trade of crop products contribute to the alleviation of global nitrate leaching risks - Xuchong Chen; Ling Liu; Yu Lu; Xuan Wang; Zhaohai Bai; Lin Ma (Global Environmental Change, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Layer-by-layer assembly mechanism of particulate-continuous phase for sandwich-like nanoparticles in oral colon-targeted protein delivery - Wen-Xuan Hu; Chang-Sen Jin; Si-Lin Li; Jia-Yang Fu; Liang-Sen Liao; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Identification of segment joint and automatic segmentation for shield tunnel based on LiDAR detection - Shui-Long Shen; Jia-Xuan Zhang; Yu-Lin Chen; Annan Zhou (Tunnelling and Underground Space Technology, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Two new ursane type triterpenoids from adult leaves of Cyclocarya paliurus - Shan-Xuan Zhang; Meng-Fei Liu; Yu-Ling Tan; Jin-Long Duan; Qiao-Lin Xu; Jian-Wen Tan (Phytochemistry Letters, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

Effects of alkaline water-assisted tea polyphenol soaking on the physicochemical, biochemical, bacterial structure, and free amino acid composition of grass carp fillets during storage at 4 °C - Yilin Lin; Xie Xuan; Kabore Manegdebwaoga Arthur Fabrice; Yigang Yu; Lihua Huang; Yehui Zhang (Food Control, 2025)

Research on Optimization Design of Ice-Class Ship Form Based on Actual Sea Conditions - Yu Lu; Xuan Cao; Jiafeng Wu; Xiaoxuan Peng; Lin An; Shizhe Liu (Journal of Marine Science and Engineering, 2025)
With the natural evolution of the Arctic route and advancements in related technologies, the development of new green ice-class ships is becoming a key technological breakthrough for the global shipbuilding industry. As a special vessel form that must perform icebreaking operations and undertake long-distance ocean voyages, an ice-class ship requires sufficient icebreaking capacity to navigate ice-covered water areas. However, since such ships operate for most of their time under open water conditions, it is also crucial to consider their resistance characteristics in these environments. Firstly, this paper employs linear interpolation to extract wind, wave, and sea ice data along the route and calculates the proportion of ice-covered and open water area in the overall voyage. This provides data support for hull form optimization based on real sea state conditions. Then, a resistance optimization platform for ice-class ships is established by integrating hull surface mixed deformation control within a scenario analysis framework. Based on the optimization results, comparative analysis is conducted between the parent hull and the optimized hull under various environmental resistance scenarios. Finally, the optimization results are evaluated in terms of energy consumption using a fuel consumption model of the ship’s main engine. The optimized hull achieves a 16.921% reduction in total resistance, with calm water resistance and wave-added resistance reduced by 5.92% and 27.6%, respectively. Additionally, the optimized hull shows significant resistance reductions under multiple wave and floating ice conditions. At the design speed, calm water power and hourly fuel consumption are reduced by 7.1% and 7.02%, respectively. The experimental results show that the hull form optimization process in this paper can take into account both ice-region navigation and ice-free navigation. The design ideas and solution methods can provide a reference for the design of ice-class ships.

A modeling framework for assessing the future changes in the occurrence of extreme rain-induced landslides - Xinlong Zhang; Qigen Lin; Manhoi Lok; Taosheng Huang; Xuan Yu; Weiping Wang; Ping Shen (Gondwana Research, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Chemical looping of catalytic methane decomposition with reverse Boudouard reaction using dual functional Ni-FeOx nanoparticle cluster for CO2-negative H2 production - Chien-Wei Wu; Zhi Xuan Law; Yu-Chun Zeng; Kun-Han Lin; De-Hao Tsai (Chemical Engineering Journal, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Aggregative Infestation of Nine Bostrichidae Species on the Madagascar Almond Tree, Terminalia neotaliala Capuron (Myrtales: Combretaceae) - Xiao-Lu Cao; Li Yu; Jian-Song Wei; Qiu-Hong Tao; Qian Lu; Wan-Xuan Wei; Xia-Lin Zheng (Neotropical Entomology, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Biotic plant-soil feedbacks alone do not explain why more diverse plant communities are less invasible - Hao-Ming Yuan; Xiao-Mei Zhang; Peter Alpert; Lin-Xuan He; Wei Xue; Lin Huang; Ling Peng; Fei-Hai Yu (Plant and Soil, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Strategies for crop straw management in China's major grain regions: Yield-driven conditions and factors influencing the effectiveness of straw return - Jia Cheng; Bai-Jian Lin; Jin-Sai Chen; Hong-Xuan Duan; Yuan-Feng Sun; Xin Zhao; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Comparative analyses of bacterial contamination and microbiome of broiler carcasses in wet market and industrial processing environments - Yuanyuan Zhou; Nan-lin Wang; Jin-qi Cen; Jia-tong Han; Yu-xuan Tang; Zi-qi Xu; Hang Zeng; Kurt Houf; Zhongjia Yu (International Journal of Food Microbiology, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

ω-9 monounsaturated fatty acids in Sapindus mukorossi seed oil enhance calcium deposition expression of Wharton’s jelly mesenchymal stem cells - Yu-Xuan Huang; Yen-Chung Lin; Chin-Kai Lin; Haw-Ming Huang (Tissue and Cell, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Most appropriate nozzle of six-rotor UAV for prescribed spraying liquid in tea plantation under effects of downwash flow structure in hover - Nai-Hong Hu; Wen-Xuan Zhou; Lin Zhu; Yan-Cheng Li; Xin-Yu Xie; Ru-Yan Hou; Cheng-Long Yin (Crop Protection, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Selenium-enriched Bifidobacterium longum DD98 significantly improves the efficacy of Mesalazine and Cyclosporin A in colitis mice - Yongjia Hu; Chengchen Xu; Ziqi Xu; Xuan Chen; Fei Gao; Ting Lin; Ping Yang; Shidong Kan; Yu Yin; Daijie Chen (Food Bioscience, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

Green transformation of oily sludge through geopolymer: Material properties and hydration mechanisms - Xuan Guo; Hongdi Yu; Hongyun Yao; Fawei Lin; Eslam Salama; Mona Ossman; Beibei Yan; Guanyi Chen (Chemosphere, 2024)

Expression of a novel hydrolase MhpC in Brevibacillus parabrevis BCP-09 and its characteristics for degrading synthetic pyrethroids - Yingyue Zhang; Dan Xiang; Jie Tang; Chuanning Peng; Siqi Chen; Siqi Huang; Qi Wen; Lin Liu; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Pesticide Biochemistry and Physiology, 2024)

Genotoxicity and cytotoxicity in male reproductive cells caused by sediment pollutants - Meng-Wei Lin; Jai-Yu Chen; Yu-Xuan Ye; Wei-Yi Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Science of The Total Environment, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Critical review for the potential analysis of material utilization from inorganic industrial solid waste - Xuan Guo; Menglan Zeng; Hongdi Yu; Fawei Lin; Jingwei Li; Wenlong Wang; Guanyi Chen (Journal of Cleaner Production, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

PARP-2 mediates cardiomyocyte aging and damage induced by doxorubicin through SIRT1 Inhibition - Chaoming Huang; Xuan Zhang; Shulin Wang; Ao Shen; Tianfen Xu; Yanhong Hou; Shuhan Gao; Yongwan Xie; Yi Zeng; Jiayu Chen; Runxiang Lin; Yu Zhang; et al. (Apoptosis, 2024)

Optimization of ultrasonic extraction of bioactive components from Alpiniae oxyphyllae Fructus using response surface methodology - Yuyi Liu; Ruimin Wang; Xuan Hu; Chengfeng Yu; Zexin Wang; Lin Zhang; Sixin Liu; Congfa Li (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Estimation of crop residue production and its contribution to carbon neutrality in China - Xin Zhao; Ruo-Chen Li; Wen-Xuan Liu; Wen-Sheng Liu; Ying-Hao Xue; Ren-Hua Sun; Yu-Xin Wei; Zhe Chen; Rattan Lal; Yash Pal Dang; Zhi-Yu Xu; Hai-Lin Zhang (Resources, Conservation and Recycling, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Directly capturing native fatty acid synthase from cancer cells by affinity-based probe for precise inhibitor discovery - Yuanyuan Lin; Huaqiu Lu; Jinhao Yu; Xuan Chen; Ningbo Chen; Huamin Zhang; Lu Ye; Yimin Chen; Weiyang Tang; Guizhong Xin; Jian-Liang Zhou (Chemical Engineering Journal, 2024)

Mechanism of deltamethrin biodegradation by Brevibacillus parabrevis BCP-09 with proteomic methods. - Yingyue Zhang; Jie Tang; Su Wang; Xuerui Zhou; Chuanning Peng; Hu Zhou; Dan Wang; Haoran Lin; Wenliang Xiang; Qing Zhang; Ting Cai; Xuan Yu (Chemosphere, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Molecular compositions of marine organic aerosols over the Bohai and Yellow Seas: Influence of primary emission and secondary formation - Fang Cao; Yi-Xuan Zhang; Yan-Lin Zhang; Wen-Huai Song; Yu-Xian Zhang; Yu-Chi Lin; Chaman Gul; Md. Mozammel Haque (Atmospheric Research, 2024)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Algal strains, treatment systems and removal mechanisms for treating antibiotic wastewater by microalgae - Juan Peng; Kai-Lu Cao; Si-Bo Lv; Yu-Xuan Hu; Jia Lin; Qian-Zhi Zhou; Jiang-Hai Wang (Journal of Water Process Engineering, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Evaluation of species thermal sensitivity with individual-based physiological performance - Liang Zhang; Yu-Yang Zhang; Lin-Xuan Ma; Yun-Wei Dong (Marine Environmental Research, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Design, synthesis, and biological activity of 9- O -cinnamoylberberines as novel lipid-lowering agents - Yuan Kong; Qi-Qi Xing; Yu-Xuan Tian; Lin Li; Pan Yu; Lin-Guo Zhao; Dong-Dong Li (Natural Product Research, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Opportunities and challenges for ribosome-inactivating proteins in traditional Chinese medicine plants - Yi-xuan Yang; Xin-yi Wang; Tong Lin; Yu Sun; Yi-cheng Yu; Zhen-hong Zhu (Toxicon, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Applying an air curtain to reduce surgical smoke concentration - Xuan-Huy Ninh; Hung-Yu Tzeng; Tak-Wah Wong; Yu-Ting Wu; Yao-Lung Kuo; Ming-Yeng Lin (Air Quality, Atmosphere & Health, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Efficient adsorption and photocatalytic degradation of water emerging contaminants through nanoarchitectonics of pore sizes and optical properties of zirconium-based MOFs - Jia-Xuan Tan; Zih-Yu Chen; Celine H. Chen; Ming-Feng Hsieh; Angela Yu-Chen Lin; Season S. Chen; Kevin C.-W. Wu (Journal of Hazardous Materials, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Two new germacrane sesquiterpenoids from the inflorescences of Mikania micrantha - Tao Lou; Qiao-Lin Xu; Yu-Ling Tan; Shao-Bo Liu; Shan-Xuan Zhang; Ying Zeng; Feng-Qiang Jiang; Jian-Wen Tan (Phytochemistry Letters, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Facile synthesis of triazine-based microporous organic network for high-efficient adsorption of flumequine and nadifloxacin: A comprehensive study on adsorption mechanisms and practical application potentials - Zhe Zhao; Shumin Lin; Zhendong Yu; Ming Su; Bolong Liang; Shu-Xuan Liang; Xue-Hai Ju (Chemosphere, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

The tiered transaction system for sea use rights in China: Theoretical basis and market construction - Xuan Yu; Sen Lin; Weiteng Shen; Qi Chen (Marine Policy, 2023)

Prenatal exposure to phthalates and polybrominated diphenyl ethers on neonatal health: A birth cohort study in Guangxi, China - Bo Qian; Zhao-xuan Zheng; Lei Yang; Cheng-qiang Wang; Yu-Chun Lin; Zhong-Ning Lin (Environmental Research, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

The Beneficial Role of Exercise on Treating Alzheimer’s Disease by Inhibiting β-Amyloid Peptide - Zi-Xuan Tan; Fang Dong; Lin-Yu Wu; Ya-Shuo Feng; Feng Zhang (Molecular Neurobiology, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Characteristics of bacterial community and ARGs profile in engineered goldfish tanks with stresses of sulfanilamide and copper - Benjamin Makimilua Tiimub; Zhen-chao Zhou; Lin Zhu; Yang Liu; Xin-Yi Shuai; Lan Xu; Christophe’ Niyungeko; Ling-Xuan Meng; Yu-Jie Sun; Hong Chen (Environmental Science and Pollution Research, 2021)

Remediation of contaminated soil and groundwater using chemical reduction and solidification/stabilization method: a case study - Shi-Feng Lu; Yu-Lin Wu; Zhan Chen; Tao Li; Chao Shen; Lin-Kang Xuan; Ling Xu (Environmental Science and Pollution Research, 2021)

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

A DEM fusion method for ascending and descending orbit StereoSAR DEMs in complicated mountain areas considering SAR echo intensity - Guo-lin Cai; Dong Shen; Ao-li Zhang; Hai-hua Yu; Xuan-yu Zhang (Journal of Mountain Science, 2021)

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Drought-tolerant plant growth-promoting rhizobacteria isolated from jujube (Ziziphus jujuba) and their potential to enhance drought tolerance - Min Zhang; Lin Yang; Ruqian Hao; Xiaoxiong Bai; Ying Wang; Xuan Yu (Plant and Soil, 2020)

Data rescue in manuscripts: a hydrological modelling study example - Xuan Yu; Anna Lamačová; Lele Shu; Christopher Duffy; Pavel Krám; Jakub Hruška; Tim White; Kairong Lin (Hydrological Sciences Journal, 2020)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Fungal spondylodiscitis in a patient recovered from H7N9 virus infection: a case study and a literature review of the differences between Candida and Aspergillus spondylodiscitis - Lie-dao Yu; Zhi-yun Feng; Xuan-wei Wang; Zhi-heng Ling; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Effects and Mechanism of Action of Ligustrazine on Isoprenaline-Induced Cardiomyocyte Hypertrophy - Xuan Xiu Ji; Xiao Li Song; Wei Qian; Xiao Lin Yu; Jian You Zhu (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Implementation of a Fast-Track Clinical Pathway Decreases Postoperative Length of Stay and Hospital Charges for Liver Resection - De-Xin Lin; Xuan Li; Qi-Wen Ye; Fen Lin; Lin-Li Li; Qi-Yu Zhang (Cell Biochemistry and Biophysics, 2011)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)